Habituation deficit of visual evoked potentials in migraine patients with hypermobile Ehlers-Danlos syndrome - Maestrini, Ilaria; Rocchi, Lorenzo; Puledda, Francesca; Viganò, Alessandro; Giuliani, Giada; Jannini, Tommaso Benedetto; Celletti, Claudia; Altieri, Marta; Camerota, Filippo; Toscano, Massimiliano; Di Piero, Vittorio (Frontiers in Neurology, 2023)
Objectives: Migraine is one of the most frequent clinical manifestations of Ehlers-Danlos syndrome, hypermobile type (hEDS). The comorbidity between these two diseases has been only partially investigated. We aimed to observe whether neurophysiological alterations described in migraineurs in visual evoked potentials (VEPs) were present in hEDS patients with migraine. Methods: We enrolled 22 hEDS patients with migraine (hEDS) and 22 non-hEDS patients with migraine (MIG), with and without aura (according to ICHD-3), as well as 22 healthy controls (HC). Repetitive pattern reversal (PR)-VEPs were recorded in basal conditions in all participants. During uninterrupted stimulation, 250 cortical responses were recorded (4000 Hz sample rate) and divided into epochs of 300 ms after the stimulus. Cerebral responses were divided into 5 blocks. The habituation was calculated as the slope interpolating the amplitudes in each block, for both the N75-P100 and P100-N145 components of PR-VEP. Results: We observed a significant habituation deficit of the P100-N145 component of PR-VEP in hEDS compared to HC (p=0.002), unexpectedly more pronounced than in MIG. We observed only a slight habituation deficit of N75-P100 in hEDS, with a slope degree that was intermediate between MIG and HC. Discussion: hEDS patients with migraine presented an interictal habituation deficit of both VEPs components like MIG. Pathophysiological aspects underlying the pathology could account for the peculiar pattern of habituation in hEDS patients with migraine characterized by a pronounced habituation deficit in the P100-N145 component and a less clear-cut habituation deficit in the N75-P100 component with respect to MIG.